Analisis Kinerja Perkerasan Semi Lentur Dengan Aspal Modifikasi Asbuton dan Tafpack-Super - Komang Wira Jaya (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2012)
The semi flexible pavement is a type of pavement with opened gradation based on porous asphalt,where the continuous pore in the mix composition is filled by mortar cement. The use of mortarcement can help performing a composite pavement which combines the strength of asphalt andcement as a bond material. The objective of using this composition is to increase the strength ofasphalt from permanent deformation, cracks both in the wet condition and the temperatureincrement. In this research, Asbuton modification asphalt (15% & 20%) and Tafpack-Supermodification asphalt (5% & 10%). The evaluation of the pavement performance was conducted bycompression strength test, split tension test and Marshall stability test with temperature variationduring test were 60oC, 70oC and 80oC. Based on the research, the compression strength resultedfrom the compression strength test were fc = 15,80 kg/cm2 for A0; fc = 21,10 kg/cm2 for A15; fc =21,90 kg/cm2 for A20; fc = 16,10 kg/cm2 for T5 and fc = 16,20 kg/cm2 for T10; while results ofsplit tension test were ftr = 1,16 kg/cm2 for A0; ftr = 2,42 kg/cm2 for A15; ftr = 1,83 kg/cm2 forA20; ftr = 1,78 kg/cm2 for T5 and ftr = 1,62 kg/cm2 for T10. From the durability of mixcomposition point of view in Marshall stability test at temperature of 70oC and 80oC, the resultsshowed that the Residual strength Index for Asbuton modification asphalt were more than 80%while for Tafpack-Super modification asphalt is less than 80% with a significant reduction inMarshall stability graph. From the various test results which have been done in this research, itcan be concluded that the Asbuton modification asphalt (15% & 20%) has a better performancecompared to Tafpack-Super modification asphalt (5% & 10%). Generally, the performance ofsemi flexible pavement tested in this research are still unsatisfied and only meet the specificationof Marshall stability for medium traffic load in the range of 550 kg up to 800 kg, while theMarshall stability required for high traffic load are 800 kg to 1.800 kg.